Cross-Generational Valuing Among Peer Academic Librarians - Munde, Gail; Coonin, Bryna (My University, 2015)
This study investigated the skills, knowledge, abilities or dispositions that are most valued and respected by academic librarians, and determined how these qualities might, or might not, be associated with generational membership. Other variables included institutional classification, career length, years since first professional degree, and broad library job function. The article explains survey design, proportional random sampling method, statistical analyses and tests, and resulting findings that may have implications for recruitment, mentoring, succession planning, and for assisting in the transmission of knowledge among academic librarians, especially from career mature librarians to their younger colleagues.